2009
DOI: 10.1186/1479-5876-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in vitamin D status and anti-microbial peptide levels in patients in the intensive care unit with sepsis

Abstract: BackgroundVitamin D insufficiency is common in hospitalized patients. Recent evidence suggests that vitamin D may enhance the innate immune response by induction of cathelicidin (LL-37), an endogenous antimicrobial peptide produced by macrophages and neutrophils. Thus, the relationship between vitamin D status and LL-37 production may be of importance for host immunity, but little data is available on this subject, especially in the setting of human sepsis syndrome and other critical illness.MethodsPlasma conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
331
6
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(382 citation statements)
references
References 29 publications
23
331
6
17
Order By: Relevance
“…7,28,32 When Toll-like receptors on macrophages bind bacterial wall lipopolysaccharide, 1-a-hydroxylase and VDR expression is upregulated, resulting in the local conversion of 25(OH)D to 1,25(OH) 2 D, which in turn increases the expression of bactericidal proteins, cathelicidin, and beta defensin. 14 Cathelicidin transcription is particularly dependent on sufficient circulating levels of 25(OH)D. 14,33 The findings of the present study are consistent with these biologic principles and other epidemiologic reports linking low serum 25(OH)D levels to increased risks of infection in the nondialysis population. 34,35 The present study makes an important contribution to the literature by demonstrating this association in the chronic dialysis population and provides another plausible mechanism for the well known impaired immunity in these patients.…”
Section: Discussionsupporting
confidence: 81%
“…7,28,32 When Toll-like receptors on macrophages bind bacterial wall lipopolysaccharide, 1-a-hydroxylase and VDR expression is upregulated, resulting in the local conversion of 25(OH)D to 1,25(OH) 2 D, which in turn increases the expression of bactericidal proteins, cathelicidin, and beta defensin. 14 Cathelicidin transcription is particularly dependent on sufficient circulating levels of 25(OH)D. 14,33 The findings of the present study are consistent with these biologic principles and other epidemiologic reports linking low serum 25(OH)D levels to increased risks of infection in the nondialysis population. 34,35 The present study makes an important contribution to the literature by demonstrating this association in the chronic dialysis population and provides another plausible mechanism for the well known impaired immunity in these patients.…”
Section: Discussionsupporting
confidence: 81%
“…The severity of an infection is negatively correlated to serum vitamin D concentrations. These findings proposed another important role for this vitamin in the progression of sepsis pathogenesis (11)(12)(13). The…”
Section: Introductionmentioning
confidence: 94%
“…29,30 A study 31 of 80 patients who came to the emergency department because of suspected infection indicated that patients with serum levels of 25-hydroxyvitamin D less than 30 ng/mL had a higher incidence of severe sepsis within 24 hours than did patients with higher serum levels. Additionally, a recent retrospective cohort study 32 of more than 3000 patients indicated that risk for sepsis was 1.6-fold higher in critically ill patients with serum levels of 25-hydroxyvitamin D less than 15 ng/mL compared with patients in the cohort with 25-hydroxyvitamin D concentrations of 30 ng/mL or higher.…”
Section: Multivariate Analysismentioning
confidence: 99%